Research Progress on the Impact of Biological Soil Crusts on Soil Nutrients and Carbon Cycling - Zhang, Jinyang; Zhang, Jing; Lei, Na (International Journal of Natural Resources and Environmental Studies, 2025)
Biological Soil Crusts (BSCs) are complex surface structures of the ecosystem formed by cryptogams such as cyanobacteria, lichens, and bryophytes, together with soil microorganisms. They are widely distributed in arid and semi - arid regions. In recent years, the ecological functions of BSCs in soil nutrient cycling and carbon sequestration have gradually become a research hotspot. This paper reviews the regulatory mechanisms of BSCs on soil nutrients such as nitrogen, phosphorus, and organic matter, analyzes their contributions and potential impacts on the global carbon cycle, and discusses the threats of climate change and human disturbances to the functions of BSCs. Future research needs to further quantify the regional carbon sequestration capacity of BSCs and develop BSC - based ecological restoration technologies.